Dulaglutide is cardioprotective with or without background metformin in patients with diabetes and established or high risk for coronary vascular disease. A subgroup analysis of the REWIND Trial. (25th November 2020) - Ferrannini, G; Gerstein, H.C; Colhoun, H.M; Dagenais, G.R; Diaz, R; Dyal, L; Lakshmanan, M; Mellbin, L; Probstfield, J; Riddle, M.C; Shaw, J.E; Ryden, L
Abstract: Background: The 2019 ESC/EASD European Guidelines for Diabetes, Prediabetes and Coronary Artery Disease introduced a paradigm shift in the management of patients with type 2 diabetes (T2D) at high risk for or already established cardiovascular (CV) disease by recommending a GLP-1 receptor agonist (GLP-1 RA) as initial glucose lowering therapy in patients without any previous antihyperglycaemic treatment. This recommendation has been questioned since outcome trials of GLP-1-RA were usually conducted with metformin as background therapy. Purpose: The aim of this report is to determine whether the effect of dulaglutide on cardiovascular events varies according to baseline metformin therapy. It was tested by a subgroup analysis of the Researching Cardiovascular Events with a Weekly Incretin in Diabetes (REWIND) trial. Methods: REWIND, a multicentre, double-blind, placebo-controlled trial, comprised 9901 participants (women: 46.3%; mean age: 66.2 years) with T2D and either a previous CV event (31%) or a high CV risk (69%). They were randomised (1:1) to either sc. dulaglutide (1.5 mg/week) or placebo in addition to standard of care. The primary outcome was the first of a composite of non-fatal myocardial infarction or stroke or CV death. Secondary outcomes were a microvascular composite endpoint, all-cause death and heart failure. The effect of dulaglutide study outcomes in patients with and without baseline metformin was evaluated by means of a Cox regression hazard model with baseline metformin, dulaglutide assignment and the interaction between dulaglutide and metformin as independent variables. Adjusted hazard ratios (HR) and 95% confidence intervals (CI) were estimated using a Cox regression model with additional adjustments for factors that differed at baseline between people on vs. those not on baseline metformin selected by a backward regression model. A p<0.05 was considered significant (see Figure 1). Results: Patients without metformin at baseline (n=1864; 19%) were older, leaner, more likely to be women and had a higher proportion of prior CV events, heart failure and renal disease than patients with metformin (n=8037; 81%). During a median follow-up of 5.4 years (IQR 5.1–5.9), the primary outcome occurred in 976 (12%) participants with baseline metformin and in 281 (15%) without metformin. There was no significant difference in the effect of dulaglutide on the primary outcome in the groups with vs. without metformin at baseline (HR 0.93 [CI 0.82–1.06] vs. 0.78 [CI 0.61–0.99]; p for interaction=0.16). The effect of dulaglutide on the secondary outcomes was also not modified by concomitant metformin use (all interaction p>0.1). Conclusion: This exploratory analysis suggests that the cardioprotective effect of dulaglutide does not depend on baseline metformin therapy. This supports the recommendation of using agents with proven cardioprotective efficacy without metformin in patients with diabetes and additional cardiac risk factors. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Eli Lilly and Company